Cerrado wetlands: multiple ecosystems deserving legal protection as a unique and irreplaceable treasure - Durigan, Giselda; Munhoz, Cássia Beatriz; Zakia, Maria José Brito; Oliveira, Rafael S.; Pilon, Natashi A.L.; Valle, Raul Silva Telles do; Walter, Bruno M.T.; Honda, Eliane A.; Pott, Arnildo (Perspectives in ecology and conservation, 2022)
[Display omitted] •Wetlands function as the “kidneys of the planet”, assuring water supply and quality.•Cerrado wetlands have distinct vegetation types playing equivalent ecological roles.•All types of Cerrado wetlands should have the same status of legal protection.•The maximum water-table elevation defines the wetlands’ limit, biota and functioning.•All human actions threatening the hydrology of Cerrado wetlands must be regulated. Wetlands are ecosystems at the interface between terrestrial and aquatic environments, subject to flooding by shallow waters or with temporarily to permanently waterlogged soils and specialized biota. Despite their great importance at global and local scales, these ecosystems have not been effectively protected in Brazil. The Cerrado wetlands are particularly neglected and misunderstood due to their distinctive hydrological functioning, imprecise maps, and multiplicity of vegetation types (e.g., wet grassland, vereda, palm grove, wet forest, gallery forest) that form complex and dynamic mosaics. Regional denominations of these wetlands often have subtle differences or redundancy, hindering their objective differentiation even by specialists. Regardless of vegetation differences, however, all Cerrado wetlands store and filter excess rainwater from the entire watershed, releasing it throughout the year to feed perennial streams and, ultimately, all of the main Brazilian rivers. Therefore, we argue that: (i) all wetlands in the Cerrado shall be unified in the legend of official large-scale maps that support environmental legislation; (ii) all vegetation types in Cerrado wetlands shall receive a unified treatment in the legislation, aligned with other wetlands in Brazil; (iii) the delimitation of wetlands for law compliance must be done on site, using objective indicators (hydrological, edaphic and botanical). We propose that all areas where the maximum elevation of the water table is less than 50 cm deep shall be mapped and protected as wetlands. That is the critical factor determining the hydromorphic soils and the specialized flora that differentiates these wetlands from the surrounding vegetation types in the Cerrado.